A cast of shadow on adjuvant radiotherapy for prostate cancer: A critical review based on a methodological perspective. (January 2016) - Arcangeli, Stefano; Ramella, Sara; De Bari, Berardino; Franco, Pierfrancesco; Alongi, Filippo; D'Angelillo, Rolando M.
Highlights: We focused on the applicability of data from RCTs in daily clinical practice. We have employed an analytical framework based on PICO criteria to refine the search. We analyzed 3 large RCTs regarding the use of RT after RP as adjuvant therapy. We concluded that the role of adjuvant RT could be reconsidered. Abstract: Objective: To perform a critical review focusing on the applicability in clinical daily practice of data from three randomized controlled trials (RCTs): SWOG 8794, EORTC 22911, and ARO/AUO 96-02. Methods and materials: An analytical framework, based on the identified population, interventions, comparators, and outcomes (PICO) was used to refine the search of the evidence from the three large randomized trials regarding the use of radiation therapy after prostatectomy as adjuvant therapy (ART). Results: With regard to the inclusion criteria: (1) Population: in the time since they were designed, in two among three trial (SWOG 8794 and EORTC 22911) patients had a detectable PSA at the time of randomization, thus representing de facto a substantial proportion of patients who eventually received salvage RT (SRT) at non-normalised PSA levels rather than ART. (2) Interventions: although all the trials showed the benefit of postoperative ART compared to a wait-and-see approach, the dose herein employed would be now considered inadequate; (3) Comparators: the comparison arm in all the 3 RCTs was an uncontrolled observation arm, where patients who subsequently developed biochemical failure were treated in various ways, with up to half of them receiving SRT at PSA well above 1 ng/mL, a level that would be now deemed inappropriate; (4) Outcomes: only in one trial (SWOG 8794) ART was found to significantly improve overall survival compared to observation, with a ten-year overall survival rate of 74% vs. 66%, although this might be partly the result of imbalanced risk factors due to competing event risk stratification. Conclusions: ART has a high level of evidence due to three RCTs with at least 10-year follow-up recording a benefit in biochemical PFS, but its penetrance in present daily clinics should be reconsidered. While the benefit of ART or SRT is eagerly expected from ongoing randomized trials, a dynamic risk-stratified approach should drive the decisions making process.